2021
DOI: 10.5194/acp-21-13687-2021
|View full text |Cite
|
Sign up to set email alerts
|

Modelling spatiotemporal variations of the canopy layer urban heat island in Beijing at the neighbourhood scale

Abstract: Abstract. Information on the spatiotemporal characteristics of Beijing's urban–rural near-surface air temperature difference, known as the canopy layer urban heat island (UHI), is important for future urban climate management strategies. This paper investigates the variation of near-surface air temperatures within Beijing at a neighbourhood-scale resolution (∼ 100 m) during winter 2016 and summer 2017. We perform simulations using the urban climate component of the ADMS-Urban model with land surface parameters… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…At night, as the suburbs were cooled by longwave radiation from the ground, while urban areas released building heat storage and anthropogenic heat emissions, the massive temperature difference between urban and rural sites increased the intensity of the heat island, and the maximum UHI intensity reached approximately 68C on the nights of 28 and 29 August. Biggart et al (2021) also showed the results that summer daytime cold island and nighttime UHI in Beijing.…”
Section: A Diurnal Variation and Spatial Distribution Of Uhimentioning
confidence: 84%
“…At night, as the suburbs were cooled by longwave radiation from the ground, while urban areas released building heat storage and anthropogenic heat emissions, the massive temperature difference between urban and rural sites increased the intensity of the heat island, and the maximum UHI intensity reached approximately 68C on the nights of 28 and 29 August. Biggart et al (2021) also showed the results that summer daytime cold island and nighttime UHI in Beijing.…”
Section: A Diurnal Variation and Spatial Distribution Of Uhimentioning
confidence: 84%
“…Most satellites are not able to provide continuous record at short intervals due to orbit and revisit period constraints, and so are ineffective in monitoring and modelling the nocturnal UHI. The 3D nature of cities, in particular restricts sensor's potential to view all surfaces [14].Computational model simulation includes the 3D tools or software to investigate the effect of the urban morphology on wind velocity, thermal comfort, temperature variations, and spatial distribution of air pollution and also helps in comparing the effects of urban planning purposes on local climate zone [15]. At an appropriate scale, computational simulation can help to bridge the spatial gap between the surface based field observations, which are generally local and remote sensing data, which are not able to determine all related thermal fluxes, despite considerable improvement in the resolution and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Ichinose et al, 1999;Fan and Sailor, 2005), subsequently contributing to higher cooling demand for buildings (Santamouris et al, 2001;Takane et al, 2019). In winter Q F can contribute to the intensity of the urban heat island (Biggart et al, 2021).…”
Section: Introductionmentioning
confidence: 99%